Design of a Microcontroller Based System to Implement 4-Electode Focused Impedance Method (FIM) (Bangladesh Journal of Medical Physics, 2013)
Designing of electronic circuitry and development of necessary software has been performed in the present work for a microcontroller based 4-electrode Focused Impedance measurement system. This needs a complex sequential analog switching of constant current ac signal generator and a potential measuring unit to 4 electrodes on the object under study. The performances of the designed system and the developed microcontroller software have been studied using a commercially available simulation software, Proteus-7, and the results are very satisfactory. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14690 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 75-79